The Role of Group Communication in Volunteer Self-Concept at Sikkola Rakyat Kota Medan - Icha Listya Sitepu; Laila Rohani (Jurnal IPTEK Bagi Masyarakat, 2026)
This study aims to analyze the role of group communication in the self-concept of volunteers at Sekolah Rakyat Kota Medan. This research employed a descriptive qualitative approach involving five volunteers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that group communication takes place through face-to-face interactions and online communication used for coordination, discussion, and activity evaluation. Through these communication processes, volunteers perceive themselves as more confident, open, and empathetic individuals. Supporting factors include a supportive environment, interaction intensity, and feedback among members, while the obstacles identified consist of misunderstandings in online communication, differences in communication styles, and low participation among some members. The study indicates that group communication plays a role in the development of volunteers’ self-concept within a community-based educational setting.